Pengaruh Keselamatan Dan Kesehatan Kerja Dalam Pelaksanaan Pembangunan Pengaman Abrasi Pantai Mampie Kecamatan Wonomulyo - Rizaldi, Muhammad Rizky; Abduh, Muhammad Natsir; Yunus, Ahmad Yauri (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
This study aims to analyze the factors that affect Occupational Health and Safety (K3) in the implementation of the construction of campie beach abrasion safety This study used quantitative methods with a descriptive approach with a total of 51 respondents. Instrument testing uses validity tests and reliability tests. While the data analysis method uses multiple linear regression with F test and t test. The results showed that the variables Workload (X1), Working Capacity (X2) and Work Environment (X3) simultaneously affect occupational safety and health (Y) in the implementation of the construction of mampie beach abrasion safety. From the calculation of the F test, F is obtained calculate 24.988 > F Table 2.73 with a sig value of 0.000 < 0.05. Based on the t test, the variables workload (X1) 2,205, working capacity (X2) 4,783, and work environment (X3) 6,612 have a positive and significant effect on occupational safety and health (Y).  In addition, the Adjusted R Square value of 0.605 which means the magnitude of the influence of the independent variable on the dependent variable is 60.50%.